Onfarm evaluation of biological nitrogen fixation potential and grain yield of Lablab and two soybean varieties in the northern Guinea savanna of Nigeria - Okogun, J.; Sanginga, Nteranya; Abaidoo, Robert C.; Dashiell, Kenton E.; Diels, J. (Springer, 2005)
Several legumes with high biological nitrogen fixation (BNF) potentials have been studied in on-station trials. The processes involved in BNF and the benefits of these species to crop production need to be evaluated using farmers' management practices in farmers' fields. An on-farm trial with 20 farmers was conducted in the northern Guinea savanna (NGS) of Nigeria. The aims were to evaluate the BNF potentials of an improved soybean variety (TGx 1448-2E) and a local variety (Samsoy-2) when inoculated with Bradyrhizobium strains, and of Lablab in farmer-managed and researcher-managed soybean-maize and Lablab-maize crop rotation systems. The level of soil P was generally low with more than 50% of the fields having less than the critical P level. The plant available P content was statistically significantly (P = 0.05) correlated with P in grain (r = 0.60), P in the shoot (r = 0.68), grain yield (r = 0.40) and nodule weight (r = 0.35). Variations in plant parameters (nodulation, shoot dry matter, percentage nitrogen derived from the air [%Ndfa], grain yield, and nutrient uptake) among and within farmers’ fields were attributed to differences in soil fertility and crop management. About 60% of the fields were moderately fertile, sufficient to support legume establishment, while about 30% of the farmers' fields had a low fertility level. For farmers in the study area to benefit from the BNF potentials of the legumes, an external P fertilizer input was necessary as well as suitable crop management practices because all parameters measured in the researcher-managed plots were higher than in the farmer-managed plots.